2003
DOI: 10.1021/ja030145g
|View full text |Cite
|
Sign up to set email alerts
|

Ureases:  Quantum Chemical Calculations on Cluster Models

Abstract: Herein, we present results from a computational study of dinickel complexes that are relevant to the catalytic hydrolysis of urea exerted by the urease enzymes. The B3LYP density functional is used to characterize the equilibrium geometry, electronic and magnetic properties, and energies for a series of realistic complexes modeling the active site of ureases. The analysis of the theoretical results gives new insight into the structure, substrate binding, and catalytic mechanism. The water bridge between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 34 publications
(61 reference statements)
11
116
0
Order By: Relevance
“…Studies showed that one of the nickel atoms bonded with the carbon atom of urea, while the other combined with the nitrogen. Similar results were presented by Andrich et al [25], who investigated the kinetics of urea degradation in a model wine solution using an acid urease and immobilized urease. The researchers determined that the reaction is a pseudo-first-order reaction.…”
Section: Enzymatic Decomposition Of Ureasupporting
confidence: 85%
“…Studies showed that one of the nickel atoms bonded with the carbon atom of urea, while the other combined with the nitrogen. Similar results were presented by Andrich et al [25], who investigated the kinetics of urea degradation in a model wine solution using an acid urease and immobilized urease. The researchers determined that the reaction is a pseudo-first-order reaction.…”
Section: Enzymatic Decomposition Of Ureasupporting
confidence: 85%
“…This last interaction has been found to determine the coordination mode of urea in QM calculations of cluster models of the urease active site. 46 Although not directly involved in urea coordination, contacts between HE2@His219, and HE2@His230 with OD2@Asp221 are readily identifiable. These residues form a His-Asp-His "triad" that remains stable over the entire MD simulation, with average inter-residue distances of 2.15Å.…”
Section: 2-structure Of the Active Sitementioning
confidence: 99%
“…[1][2][3][4] In contrast, when catalyzed by ureases, urea is generally believed to undergo hydrolysis rather than ammonia elimination. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The products of hydrolytic decomposition have been reported to be either HCO 3 − and NH 4 + or ammonium carbamate depending on the buffer system. 19 These products are most readily rationalized to arise from an addition-elimination sequence.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][29][30][31] A B3LYP study on cluster models of the active site of ureases was carried out recently. 15 Models of various resting states of the active site were modeled and investigated, and mono-and bidentate modes of urea coordination were considered. Estiu and Merz 17 tested different mechanisms of urea decomposition in the gas phase and in solution modeled by the isodensity continuum polarizable model (ICPM).…”
Section: Introductionmentioning
confidence: 99%